Diversity of arthropod soil dweller in relation to monoculture and polyculture practices in oil palm smallholdings in Selangor, Malaysia - Nasron, Amal Ghazali (2016)
Oil palm plantation has become one of the economic mainstays for biodiversityrich countries in the tropics. It plays a major role in the economy of Malaysia as the second largest producer of palm oil and oil palm related products after Indonesia. The conversion of native forests to oil palm monoculture system has caused biodiversity loss. With proper planning and implementation of farming practice, oil palm agriculture in Malaysia can go further as an economic backbone. However, little is known about the effects of oil palm polyculture system on biodiversity. Studying arthropod diversity in response to different habitat variables will give evidence to support wildlife conservation in the expanding oil palm industry. The smallholdings were chosen as representatives of the oil palm smallholdings in Peninsular Malaysia as they include both oil palm and banana plants. In this study, arthropods are used as ecological indicators while pitfall traps were used in data collection. Systematic sampling of insects with random starting points were used in pitfall trapping in each plot. Arthropod diversity was examined with respect to abundance, number of orders (order richness) and community composition responded to different farming practices and vegetation structure characteristics. Across oil palm smallholdings, the number of arthropod orders were significantly higher in polyculture smallholdings than monoculture smallholdings. However, there were no significant difference in arthropod abundances in both monoculture and polyculture smallholdings. Habitat quality variables explained 15.98% of arthropods richness. The most significant predictor variables in influencing arthropod diversity were polyculture farming practice, height of oil palm crop and number of immature oil palm. This study concluded that polyculture smallholdings can host a wider arthropod order than monoculture smallholdings. Arthropods were shown to favour multiple crops that offer variety of food sources for different trophic levels. The findings of this study suggest that, in order to preserve biodiversity, oil palm stakeholders should maintain as much of the remaining arthropod biodiversity as possible by sustaining local habitat complexity in the smallholdings. This practice is not only important for the oil palm smallholding sustainability, but it also increases arthropods richness that helps to carry out important ecological niche and functions in the oil palm landscape such as floral pollination, pest predation, decomposing of litter layer and recycling of nutrient cycle.